Seminar Akad Muamalah Perbankan Syariah Desa Kalisari: Meningkatkan Literasi Ekonomi Islam Di Masyarakat - Muhammad Husaini (https://journal.metanusantara.com/impact/index.php/jpk, 2024)
Muamalah contracts in the Islamic economic system have a fundamental role in shaping transactions that are fair, transparent, and in accordance with sharia principles. However, the community's understanding of this concept is still low, especially in the application of contracts in Islamic banking. Therefore, this research aims to improve the community's understanding of muamalah contracts through educational seminars held in Kalisari Village.This research uses a qualitative approach with anaction research method. The main data sources came from observations, interviews, and documentation during the seminar. The informants in this study were Kalisari villagers who participated in the seminar, as well as resource persons from Islamic financial institutions who provided material related to muamalah contracts. The results showed that the seminar succeeded in increasing people's understanding of various types of muamalah contracts, such as murabahah, musyarakah, and mudharabah. In addition, seminar participants began to show interest in switching from the conventional usury-based financial system to Islamic banking, which is more in line with Islamic principles. The main factor influencing this change was the hands-on education provided through interactive discussions and case studies.